A Class Of Diameter Six Graceful Trees - PANDA, AMARESH CHANDRA; Mishra, Debdas (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
In this paper we give graceful labelings to diameter six trees( a1, a2, . . . , am; b1, b2, . . . , bn; c1, c2, . . . , csatisfying the following property: m + n is odd, degree of each neighbour of a0 is even, and the centers of the branches incident on the center ai of diameter four trees are either all odd branches or all even branches.